Elimination of Mortgage Rights Over Property Rights Falling to the State Due to Land Procurement for Public Interests - Zuhria, Aminatus (International Significance of Notary, 2022)
This study aims to analyze the legal consequences of the abolition of mortgage rights released in the public interest, in addition to analyzing the protection of creditors if land rights are used as collateral for debts by debtors. This study uses a normative method which will explain the legal consequences of the abolition of mortgage rights released for public interest against the principal agreement does not eliminate the debtor's obligations in carrying out debt payments, the position of creditors due to the abolition of mortgage rights contained in the Deed of Granting Mortgage Rights (APHT) which is the accessoir agreement is deemed null and void, with the cancellation of the accessoir agreement it cannot cancel the credit agreement which is the principal agreement. and Notary/PPAT Efforts in Making APHT to Anticipate the Elimination of Mortgage Rights Notary/PPAT must continue to carry out the procedure for making a deed as stipulated in the laws and regulations. Keywords: Mortgage, Land Acquisition, Public Interest